2017
DOI: 10.1111/area.12351
|View full text |Cite
|
Sign up to set email alerts
|

Studying social practices and global practice change using scrapbooks as a cultural probe

Abstract: Empirical work on household consumption informed by theories of social practice has grown exponentially in the last few years. This is partly due to conceptual developments positing practices as being comprised of materials, meanings and skills. Such formulations are readily applied to empirical investigations. As the aim of a growing body of empirical work with theories of social practice is to present evidence for how practices can, should, have or might change in the future towards improved sustainability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…In response to critiques, practice‐researchers have developed strategies for improving the effectiveness of talk‐based methods; for example, Hitchings (2011) advocates a serial interviewing approach to allow for gradual emergence of discursive reflection. However, most practice‐theoretical studies continue to involve single‐instance interviews (Maller & Strengers, 2018). Others suggest a value in working with participants during moments of learning, disruption, and change (Giddens, 1984) which offer opportunities for intervening in practices (Sahakian et al, 2021) and developing discursive reflection (see also Rinkinen, 2013).…”
Section: Talk‐based Methods For Researching Past Practices: Challenge...mentioning
confidence: 99%
“…In response to critiques, practice‐researchers have developed strategies for improving the effectiveness of talk‐based methods; for example, Hitchings (2011) advocates a serial interviewing approach to allow for gradual emergence of discursive reflection. However, most practice‐theoretical studies continue to involve single‐instance interviews (Maller & Strengers, 2018). Others suggest a value in working with participants during moments of learning, disruption, and change (Giddens, 1984) which offer opportunities for intervening in practices (Sahakian et al, 2021) and developing discursive reflection (see also Rinkinen, 2013).…”
Section: Talk‐based Methods For Researching Past Practices: Challenge...mentioning
confidence: 99%
“…The initial research design involved collecting data through face-to-face interviews and home tours in two households. Maller and Strengers (2016) contend that a home tour ‘not only prompts participants’ memories but allows the material dimensions and skilful performance of practices to become more prominent’. Participants recounted how materials are utilised in their daily activities and showed the researcher the locus of plastic-related practices within the household.…”
Section: Methodsmentioning
confidence: 99%
“…Alternative research methods and educational programs are required, such as effective use of a diary for collective residential water usage data rather than individual estimates [24]; these offer greater opportunities to discover important inter-and intra-relationships 'between whole bundles of practice that co-exist in particular domains of everyday life' [55]. For example, a practice memory scrapbook has been demonstrated to be a useful qualitative method in further engaging and uncovering everyday normative practices involved in meanings, materials and skills [90]. Where students in this research identified what they actually used as compared to what they thought they used, significant discrepancies were apparent; students typically underestimated their water use.…”
Section: Water Use: Application Of Practice Theorymentioning
confidence: 99%